Memorias colectivas de la gestión hídrica de la parroquia san francisco de Bolívar - Aponte Urrutia, Erik Arnaldo (2018)
The problem related to the history of the people requires an urgent analysis so that one can know the reason they have different traditions, customs, practices, beliefs, etc., besides the fact that there should be a general interest in the topic in order to carry out academic studies that contribute to social knowledge. In that sense, this project aims to determine the discourse generated by the collective memory around water management in the perish San Francisco de Bolívar through the socialization of the results in a public event. The methodological strategy that was implemented had a qualitative approach through the technique of focal groups: in group